2021
DOI: 10.1093/mnras/stab1174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface heterogeneity on IR line profiles of adsorbed carbon monoxide on models of interstellar grain surfaces

Abstract: Surface heterogeneity of model amorphous silica films used as a model for interstellar grain surfaces is revealed through the application of the pre-exponential optimized inversion method to previously reported sub-monolayer thermal desorption studies of carbon monoxide (CO) desorption. The impact of that surface heterogeneity, as represented by the coverage dependence of the CO activation energy for desorption from the amorphous silica surface, on the IR spectroscopy of the CO stretching vibration is explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A lower binding energy of 1418 K was measured for a 0.1 ML adsorbed on SiO x surface . Recently Taj et al reported values between 750 and 1100 K for a monolayer of CO adsorbed on amorphous SiO x . O . We used the value estimated by Minissale et al on oxidized HOPG.…”
Section: Tables Of Recommended Valuesmentioning
confidence: 96%
“…A lower binding energy of 1418 K was measured for a 0.1 ML adsorbed on SiO x surface . Recently Taj et al reported values between 750 and 1100 K for a monolayer of CO adsorbed on amorphous SiO x . O . We used the value estimated by Minissale et al on oxidized HOPG.…”
Section: Tables Of Recommended Valuesmentioning
confidence: 96%
“…coming to the fore with studies likewise on a variety of carbonaceous [168], siliceous [167,198,199] and ice surfaces [168,198,200]. As an illustrative example, we consider the study of CO desorption from amorphous silica by Taj and co-workers [198,199].…”
Section: Thermal Processesmentioning
confidence: 99%
“…coming to the fore with studies likewise on a variety of carbonaceous [168], siliceous [167,198,199] and ice surfaces [168,198,200]. As an illustrative example, we consider the study of CO desorption from amorphous silica by Taj and co-workers [198,199]. Figure 12 shows the R 2 (the sum of the squared error of the fit) data versus pre-exponential factor for these measurements.…”
Section: Thermal Processesmentioning
confidence: 99%
See 1 more Smart Citation